2007
DOI: 10.1037/0021-843x.116.3.632
|View full text |Cite
|
Sign up to set email alerts
|

Response perseveration in psychopaths: Interpersonal/affective or social deviance traits?

Abstract: In order to clarify the role of the two broad components of psychopathy (interpersonal/affective and social deviance; R. D. Hare, 2003) in explaining maladaptive response perseveration in psychopaths, as well as the role of reflection after punished responses in this deficit, the authors administered a card perseveration task to 47 Spanish male inmates assessed using the Hare Psychopathy Checklist-Revised (PCL-R; R. D. Hare, 1991). Hierarchical regressions showed that psychopaths' maladaptive perseveration (mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 29 publications
2
29
0
8
Order By: Relevance
“…First off, criminal and impulsive psychopathic individuals are characterized by unstable and inflexible cognitive processes during goal directed behavior which could underlie the automatic hyperfocus on short-term novel rewards (insufficient stability to engage in longer term endeavors) and the impaired behavioral adaptations to non-reward, punishment, or peripheral warning cues (insufficient flexibility to adjust ongoing goal-directed behavior) (Lapierre et al, 1995;Ishikawa et al, 2001;Mitchell et al, 2002;Newman and Lorenz, 2003;Blair et al, 2005;Moltó et al, 2007;Gao et al, 2011;Poythress and Hall, 2011;Dolan, 2012).…”
Section: Heterogeneity In Primary Psychopathic Samplesmentioning
confidence: 97%
“…First off, criminal and impulsive psychopathic individuals are characterized by unstable and inflexible cognitive processes during goal directed behavior which could underlie the automatic hyperfocus on short-term novel rewards (insufficient stability to engage in longer term endeavors) and the impaired behavioral adaptations to non-reward, punishment, or peripheral warning cues (insufficient flexibility to adjust ongoing goal-directed behavior) (Lapierre et al, 1995;Ishikawa et al, 2001;Mitchell et al, 2002;Newman and Lorenz, 2003;Blair et al, 2005;Moltó et al, 2007;Gao et al, 2011;Poythress and Hall, 2011;Dolan, 2012).…”
Section: Heterogeneity In Primary Psychopathic Samplesmentioning
confidence: 97%
“…First, it has been found that primary psychopathic individuals with high levels of antisocial and impulsive behavior are characterized by both a lower stability and lower flexibility of PFC mediated executive processes during goal directed behavior (Dolan, 2012;Gao et al, 2011;Ishikawa et al, 2001;Lapierre, Braun, & Hodgins, 1995;Mitchell, Colledge, Leonard, & Blair, 2002;Moltó, Poy, Segarra, Pastor, & Montañés, 2007;Poythress & Hall, 2011). This PFC processing profile could underlie the automatic hyperfocus on immediate and strong reinforcements (insufficient stability to engage in longer term endeavors; easily bored) and the impaired behavioral adaptations to non-reward, punishment, or peripheral warning cues (impaired response modulation; inability to learn from experience) as observed in disinhibited and criminal subtypes of primary psychopathy (Blair et al, 2005;Newman & Lorenz, 2003).…”
Section: Biobehavioral Pathways To Primary Psychopathymentioning
confidence: 98%
“…Una vez en el laboratorio, a los participantes se les administró una adaptación de la tarea de perseveración de cartas de Newman et al (1987), similar a la utilizada por Moltó et al (2007), en la que se registraba la latencia de respuesta tras el feedback. La presentación de la tarea y la adquisición de los datos fue controlada a través de un ordenador Pc HP workstation xw4600 con un Monitor 22» lcD tFt, mediante la aplicación Presentation v.9.2 (Neurobehavioral Systems).…”
Section: Procedimientounclassified
“…Aunque en la presente muestra subclínica las puntuaciones totales en el PPi-R no se asociaran con una perseveración de respuestas no adaptativas -como sí se ha demostrado en los estudios previos utilizando el Pcl-R en muestras penitenciarias (Newman et al, 1987;Moltó et al, 2007)-, los resultados del presente trabajo son consistentes con la propuesta de que el diagnóstico de psicopatía del PPi-R, más que representar un constructo unitario (como es la evaluación de la psicopatía a partir del Pcl-R), constituye un rasgo multifacético que emerge a partir de rasgos de orden menor, que pueden no estar relacionados entre sí o mostrar relaciones opuestas (Lilienfeld y Widows, 2005). El hecho de que la escala de Ausencia Despreocupada de Planes, tras controlar la varianza compartida con el resto de subescalas, se asociara con una perseveración de respuestas no adaptativas en la cPt y con un estilo de juego caracterizado por una falta de reflexión general tras el feedback, constituye un soporte empírico a la medida que ofrece dicha subescala, ya que precisamente refleja las caracterís-ticas de impulsividad que tradicionalmente se han asociado a la psicopatía.…”
Section: Discusión Y Conclusionesunclassified
See 1 more Smart Citation